The Effect of Perceived Price and Facilities on Customer Satisfaction at Soedirman Guest House Tulungagung - Christiano, Nicolas Raynato; Purwanto, Sugeng; Amriel, Egan Evanzha Yudha (Journal of Social Research, 2023)
The hospitality industry is one of the most competitive business sectors, including in Tulungagung. In an effort to maintain and increase market share, it is important for Soedirman Guest House to understand the factors that influence customer satisfaction. Price perceptions and facilities are two factors that have a significant influence on customer satisfaction. This study aims to examine the effect of perceived price and facilities on customer satisfaction at Soedirman Guest House in Tulungagung. This study uses quantitative research methods. The data collection technique was carried out with a questionnaire measured on a Likert scale. The population used in this study were all Soedirman Guest House consumers. The sampling technique used was Accidental Sampling. Hypothesis testing in this study was carried out with a Structural Equation Model (SEM) based on Partial Least Square (PLS). The results showed that the perception of price and facilities was able to make a good contribution to customer satisfaction at Soedirman Guest House. This shows that the better the price perception that consumers have and the more complete and adequate the facilities owned by the guest house, it will make Soedirman Guest House consumers feel satisfied.